Russland und der Vergleich zwischen Imperien.: Einige Anknüpfungspunkte - Osterhammel, Jürgen (Comparativ, 2008)
Russia and the Comparison between Empires The Russian Empire usually occupies its settled place within dichotomies of East vs. West and land-based vs. continental empires. The article tries to transcend these conventional constraints. It situates the Russian empire within a broader range of neighboring cases including China, the Muslim empires and also frontier expansion in the Western hemisphere. In a comparative perspective, several features which appear to be uniquely Russian or Eastern European lose their distinctiveness. Thus, notions of Russian exceptionalism are opened for reconsideration.